2020
DOI: 10.3389/fpsyt.2020.00512
|View full text |Cite
|
Sign up to set email alerts
|

Integration of a Return-to-Work Module in Cognitive Behavioral Therapy in Patients With Major Depressive Disorder and Long-Term Sick Leave—A Feasibility Study

Abstract: Objective: Major depressive disorder (MDD) has a negative impact on individuals ability to work, and is often associated with long phases of sick leave. Consequently, interventions facilitating return to work in patients with MDD gained increased attention during last decades. We here report results of a feasibility study where a "return-to-work" (RTW) module published by Lagerveld and colleagues in the Netherlands was integrated in cognitive behavioral therapy in depressed patients with long-term sick leaves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…Our results are close to those reported by Ito et al's [17] pilot study, whereby work-focused cognitive behavioral group therapy (8 sessions) for Japanese workers on sick leave due to depression resulted in improvements in anxiety and depressive symptoms, as well as in social functioning from pre to post intervention. Our results are also close to those of Winter et al [46], who conducted a pilot study with 20 German workers with a major depression who received cognitivebehavioral therapy, with an integrated, standardized RTW module (W-CBT). They also found that work ability significantly improved and depressive symptoms were significantly reduced in their pre-post comparison.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results are close to those reported by Ito et al's [17] pilot study, whereby work-focused cognitive behavioral group therapy (8 sessions) for Japanese workers on sick leave due to depression resulted in improvements in anxiety and depressive symptoms, as well as in social functioning from pre to post intervention. Our results are also close to those of Winter et al [46], who conducted a pilot study with 20 German workers with a major depression who received cognitivebehavioral therapy, with an integrated, standardized RTW module (W-CBT). They also found that work ability significantly improved and depressive symptoms were significantly reduced in their pre-post comparison.…”
Section: Discussionsupporting
confidence: 90%
“…Given that depressive and anxiety symptoms can negatively impact one's RTW, it is important to consider both clinical and work outcomes when evaluating RTW and work sustainability. Recent developments for preventing sustained or recurrent depressive symptoms after RTW can be found in the literature, mostly favoring interventions using cognitive behavioral concepts and strategies, either in group or individual formats [16,17,46]. According to Arends et al's [24] trajectory analyses following RTW after a CMD-related sick leave, workers continue to experience work functioning and clinical challenges over time, even at one-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding interventions addressing the individual we found eight different interventions [15,16 ▪ ,19,24–26,27 ▪ ,30] from Europe, the United States, Canada and Japan. Most of them were complex and elaborate interventions being based on cognitive behavioural therapy and/or vocational rehabilitation.…”
Section: Resultsmentioning
confidence: 99%
“…Participants (employees with psychological complaints) can be transferred to the program by their occupational health physicians, their supervisors or by self-assignment. Winter et al [19] evaluated the feasibility of a CBT program that focussed on RTW over an average of 26 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…However, studies concerning the effects of exercise interventions on work ability in psychologically burdened, non-clinical samples are scarce. Depression and anxiety are associated with more sick-days at the workplace, earlier retirement, and less productivity compared to individuals without diagnosed depression and anxiety (41)(42)(43)(44). Some studies have been published highlighting psychotherapeutic approaches to improve return-to-work in patients with depression and anxiety, either using face-to-face psychotherapy or internet based devices (45,46).…”
Section: Discussionmentioning
confidence: 99%